Analisis Penerapan Sistem Mudharabah Pada Bank Muamalat Dikota Tidore Kepulauan - Imran Yunus (Peneliti.net, 2022)
This study aims to analyze how the mudaraba financing system in companies and to compare and apply the theories that have been obtained with the implementation of Islamic banking in order to determine the extent to which these theories can be applied in the Islamic banking system. The data analysis method used is a quantitative method using multiple linear regression. The data used are primary and secondary data, data collection techniques used are observation and interview techniques. The results of this study indicate that the application of the mudharabah system at Bank Muamalat City of Tidore Islands has met the principles of sharia. Similarly, the implementation of these products in general